Poezija kot izhodišče ustvarjalnega procesa (bodočih) vzgojiteljev na - Jurjevič, Nuša; Geršak, Vesna (Otrok in knjiga, 2025)
Poetry as a starting point for the creative process of (future) educators at the intersection of art and modern technologies. In the paper, we describe a study process in which prospective preschool teachers created multimodal stop-motion animations, using a poem as a starting point. The study ascertains that (future) educators see this type of work as a positive contribution to their competencies, their attitude towards modern technologies, as well as their pedagogical practice.
Keywords: poetry; stop-motion animation; multimodality; competent educators; digital skills